Interleukin 4 promotes phagocytosis of murine leukemia cells counteracted by CD47 upregulation - Pablo Peña-Martínez; Ramprasad Ramakrishnan; Carl Högberg; Caroline Jansson; David Gisselsson Nord; Marcus Järås (Haematologica, 2021)
Cytokines are key regulators of tumor immune surveillance by controlling immune cell activity. Here, we investigated whether interleukin 4 (IL4) has antileukemic activity via immune-mediated mechanisms in an in vivo murine model of acute myeloid leukemia driven by the MLL–AF9 fusion gene. Although IL4 strongly inhibited leukemia development in immunocompetent mice, the effect was diminished in immune-deficient recipient mice, demonstrating that the antileukemic effect of IL4 in vivo is dependent on the host immune system. Using flow cytometric analysis and immunohistochemistry, we revealed that the antileukemic effect of IL4 coincided with an expansion of F4/80+ macrophages in the bone marrow and spleen. To elucidate whether this macrophage expansion was responsible for the antileukemic effect, we depleted macrophages in vivo with clodronate liposomes. Macrophage depletion eliminated the antileukemic effect of IL4, showing that macrophages mediated the IL4-induced killing of leukemia cells. In addition, IL4 enhanced murine macrophage-mediated phagocytosis of leukemia cells in vitro. Global transcriptomic analysis of macrophages revealed an enrichment of signatures associated with alternatively activated macrophages and increased phagocytosis upon IL4 stimulation. Notably, IL4 concurrently induced Stat6-dependent upregulation of CD47 on leukemia cells, which suppressed macrophage activity. Consistent with this finding, combining CD47 blockade with IL4 stimulation enhanced macrophage-mediated phagocytosis of leukemia cells. Thus, IL4 has two counteracting roles in regulating phagocytosis in mice; enhancing macrophage-mediated killing of leukemia cells, but also inducing CD47 expression that protects target cells from excessive phagocytosis. Taken together, our data suggest that combined strategies that activate macrophages and block CD47 have therapeutic potential in acute myeloid leukemia.